2013
DOI: 10.1016/j.clinph.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Ten years on: A follow-up review of ERP research in attention-deficit/hyperactivity disorder

Abstract: This article reviews the event-related potential (ERP) literature in relation to attention-deficit/hyperactivity disorder (AD/HD) over the years [2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012]. ERP studies exploring various aspects of brain functioning in children and adolescents with AD/HD are reviewed, with a focus on group effects and interpretations in the domains of attention, inhibitory control, performance monitoring, non-pharmacological treatments, and ERP/energetics interactions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 83 publications
(130 reference statements)
11
132
0
6
Order By: Relevance
“…The preferred states generally amplified P3, a finding that would be interesting to pursue in other paradigms. Further, noting that impaired P3 is often observed in clinical samples (such as AttentionDeficit/Hyperactivity disorder; see review in Johnstone et al, 2013), this result suggests that dysfunction in this mechanism may be worth investigation in such groups. Also, preferred brain states contributed to the distinctive Go/NoGo P3 topographies (anteriorisation of the NoGo P3; .…”
Section: Summary and Future Researchmentioning
confidence: 94%
“…The preferred states generally amplified P3, a finding that would be interesting to pursue in other paradigms. Further, noting that impaired P3 is often observed in clinical samples (such as AttentionDeficit/Hyperactivity disorder; see review in Johnstone et al, 2013), this result suggests that dysfunction in this mechanism may be worth investigation in such groups. Also, preferred brain states contributed to the distinctive Go/NoGo P3 topographies (anteriorisation of the NoGo P3; .…”
Section: Summary and Future Researchmentioning
confidence: 94%
“…An especially important factor is performance monitoring, which is vital for adapting one's own behavior and enabling effective cognitive control. Error monitoring and feedback processing are two important facets of performance monitoring [4,5]. As a critical function of the human cognitive system, error monitoring is the ability to monitor and evaluate the outcomes and consequences of behavior in order to optimize and adapt subsequent behavior to realize goals such as driving vehicles, the rendezvous and docking (RAD) in human spaceflight, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Early ERP studies of childhood ADHD predominantly investigated auditory and visual attention systems, and found alterations at various stages of information processing (for a review, see Barry, Johnstone, & Clarke, 2003). Recently, this line of ERP research has focused on inhibitory control, performance monitoring, and ERP/energetic interactions (for a review, see Johnstone, Barry, & Clarke, 2013). These studies showed that ADHD and TD groups markedly differed in the ERP correlates of early orienting, inhibitory control, and error processing .…”
mentioning
confidence: 99%